(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The focus of this research work was to investigate the influence of information retrieval skills on behavioural intention to use electronic information resources by MBA students in Nigeria federal universities. Cluster sampling technique was adopted for the study and systematic sampling technique was used to select 60% of the total population of the MBA students across the ten federal universities offering the programme based on probability and proportionate size. Data were collected using questionnaire designed to elicit response from respondents and analysed using Pearson Product Moment Correlation Analysis, Multiple Regression Analysis using Partial Lease Square Method (PLSEM), Mean, Standard Deviation and Percentages. However, out of one thousand two hundred and seventy (1,270) copies of questionnaire administered to the respondents, one thousand and fifteen copies (1,015) were returned which represents 79.9% response rate for the study. Findings revealed that the level of information retrieval skills among MBA students in Nigeria universities was high. However, the results of the study established that information retrieval skills of MBA students predicted their behavioural intention to use electronic information resources, which an important and life-long skill in the current information economy.